The qualitative researcher as a bricoleur and a bedspread maker - Giovana Calcagno Gomes (Rev Rene)
The first researches with qualitative approach were developed under the positivist focus in the decades of 1920 and 1930. A number each time larger of qualitative researchers in the field of health is observed. In the nursing area this type of research has been gradually increasing, a fact which is proved by the crescent number of articles, papers and thesis in this approach with the use of different methods in the search for improvement in the care of nursing. The qualitative research has had an important role in the construction of knowledge regarding the beliefs, experiences, ways of life, meanings, allowing the free expression of the perceptions and the subjectivity of the human beings, emphasizing the reality of the participants, thus providing them the right to expresses themselves. It originally came from a concern to understand the other, providing visibility to the experienced world, to their daily lives.